2021
DOI: 10.4067/s0718-221x2022000100401
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of CNC operating parameters to minimize surface roughness of Pinus sylvestris using integrated artificial neural network and genetic algorithm

Abstract: The surface roughness of wood is affected by the processing conditions and the material structure. So, optimization of operation parameters is very crucial to have minimum surface roughness. In this study, modeling and optimization of surface roughness (Ra) of Scotch pine (Pinus sylvestris) was investigated. Firstly, the samples were cut under different conditions 8 mm, 9 mm and 11mm depth of cut and 12 mm, 14 mm and 16 mm axial depth of cut) in computer numerical control (CNC) machine, and then surface roughn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…While Hazir and Ozcan (2019) found these values as 8 mm cutting tool diameter, 17377 rpm spindle speed, and 2.012 m/min feed rate for cedar wood, Hazir and Koc (2019) in another study determined as 9.88 mm cutting tool diameter, 21000 rpm spindle speed, and 2.21 m/min feed rate for beech wood. Furthermore, Gürgen et al (2022) found the optimum parameter results for pine wood as 17900 rpm spindle speed and 3 m/min feed rate. In this study, the samples with the highest wettability were obtained in walnut wood with a 4 mm cutting tool diameter, 14000 rpm spindle speed and 3 m/min feed rate while these values were determined as 3 mm cutting tool diameter, 12000 rpm spindle speed and 9 m/min feed rate in the ash wood.…”
Section: Optimization Resultsmentioning
confidence: 99%
“…While Hazir and Ozcan (2019) found these values as 8 mm cutting tool diameter, 17377 rpm spindle speed, and 2.012 m/min feed rate for cedar wood, Hazir and Koc (2019) in another study determined as 9.88 mm cutting tool diameter, 21000 rpm spindle speed, and 2.21 m/min feed rate for beech wood. Furthermore, Gürgen et al (2022) found the optimum parameter results for pine wood as 17900 rpm spindle speed and 3 m/min feed rate. In this study, the samples with the highest wettability were obtained in walnut wood with a 4 mm cutting tool diameter, 14000 rpm spindle speed and 3 m/min feed rate while these values were determined as 3 mm cutting tool diameter, 12000 rpm spindle speed and 9 m/min feed rate in the ash wood.…”
Section: Optimization Resultsmentioning
confidence: 99%
“…They are suitable for modeling various manufacturing functions due to their ability to learn complex non-linear and multivariable relationships between process parameters (Karayel, 2009). Using artificial neural networks (ANNs) have been applied in wood and wood-based materials science and the wood machining industry, such as in recognition of wood species (Esteban et al, 2009), the drying of solid wood (Wu and Avramidis, 2007) the mechanical properties (Fernández et al, 2012;Tiryaki and Aydin, 2014), machining parameters optimization (Sofuoglu, 2015;Gurgen et al, 2021), wood surface roughness (Ayanleye et al, 2021;Gurgen et al, 2021) the classification of wood and wood-based materials defects (Avramidis and Iliadis, 2005;Pan et al, 2021), the analysis of moisture (Zhang et al, 2016), noise emission in the machining of wood (Ozşahin and Singer, 2022) and fracture toughness of wood (Samarasinghe and Jamieson, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Usually, when measuring the texture of a machined surface, it is the roughness that is analyzed, while waviness and shape deviation are the elements that are filtered out of the collected data. Roughness can occur as a result of processing conditions and regimes, or as a result of the internal structure of the wood's anatomical structure [1].…”
Section: Introductionmentioning
confidence: 99%